2019
DOI: 10.1016/j.jsxm.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Outcome Following Distal Shunt and Tunneling for Treatment İschemic Priapism: A Single-Center Experience

Abstract: Background Ischemic priapism (IP) is a urologic emergency that requires early intervention. The main aim of IP treatment is to relieve the cavernosal pressure and provide erectile function. Aim The aim of this study was to determine the correlation between preoperative risk factors (patient’s age, duration of priapism, preoperative erectile function) and postoperative erectile dysfunction (ED). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In patients with priapism < 12 hours, interstitial edema and minor endothelial defects predominate in the smooth muscle. On the contrary, extensive necrosis of the smooth muscle cells was detected after priapism lasting > 48 hours (28,29). Moreover, the presence of intravascular clots inside the cavernous sinuses causes venous obstruction and recurrent priapism (30).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with priapism < 12 hours, interstitial edema and minor endothelial defects predominate in the smooth muscle. On the contrary, extensive necrosis of the smooth muscle cells was detected after priapism lasting > 48 hours (28,29). Moreover, the presence of intravascular clots inside the cavernous sinuses causes venous obstruction and recurrent priapism (30).…”
Section: Discussionmentioning
confidence: 99%
“…These procedures can salvage unassisted erections in 15% of IP cases and erections responsive to oral medications in another 31% of men (depending on priapism duration and type of shunt). 9 Without distal corpus cavernosal surgical shunt creation, virtually all patients with persistent IP will have complete erectile dysfunction. Additionally, shunting can lead to complications such as infection, skin necrosis, urethral injury, fistula formation, and cavernositis.…”
Section: Benefits and Harmsmentioning
confidence: 99%
“…Distal corpus cavernosal surgical shunt creation, with or without tunneling, is reserved for patients who do not improve with first-line treatments or for more than 48 hours after onset of priapism. These procedures can salvage unassisted erections in 15% of IP cases and erections responsive to oral medications in another 31% of men (depending on priapism duration and type of shunt) . Without distal corpus cavernosal surgical shunt creation, virtually all patients with persistent IP will have complete erectile dysfunction.…”
Section: Benefits and Harmsmentioning
confidence: 99%
“…The overwhelming majority of studies include small patient cohorts and are retrospective in nature, except for one prospective study that included 19 patients. 4 Similarly, there are no studies comparing shunting alone versus shunting with tunneling. Four studies reporting on various distal shunts with corporal tunneling, including the Burnett snake maneuver, demonstrate generally high rates of immediate success at relieving priapism.…”
Section: Surgical Management Of Acute Ischemic Priapismmentioning
confidence: 99%
“…Erectile dysfunction (ED) is the most significant complication in patients with prolonged acute ischemic priapism, and the likelihood of developing ED is related to the length of an acute ischemic priapism event. 3–5 Bennett and Mulhall demonstrated that sickle cell patients with priapism of >36 hours had permanent ED with no men recovering erectile function, 6 and while the exact time point of irreversible smooth muscle loss is undetermined, it is recognized that smooth muscle edema and atrophy occur in as early as six hours. 3,4 As the duration of the priapism increases, patients may be refractory to first-line treatments, such as aspiration, with or without irrigation, and ICI with phenylephrine.…”
Section: Guideline Statementsmentioning
confidence: 99%